Corrigendum to “Nanofibers of N,N,N-trimethyl chitosan capped bimetallic nanoparticles: Preparation, characterization, wound dressing and in vivo treatment of MDR microbial infection and tracking by optical and photoacoustic imaging” [Int. J. Biol. Macromol. 263 (2024) 130154](S0141813024009577)(10.1016/j.ijbiomac.2024.130154) - Malik A.K.; Singh C.; Mehata A.K.; Vikas; Setia A.; Muthu M.S.; Tiwari P.; Verma D.; Mukherjee A. (My University, 2025)
The authors regret a mistake, which was entirely unintentional and occurred during the final stages of figure preparation. Specifically, during the data consolidation and visualization process, due to a labelling mistake in our repository of the same animal group, the 7B Untreated Day 4 images were mistakenly over-copied in the 7B Untreated Day 12 folder and the experimental results for Untreated Day 12 was inadvertently selected. Despite our thorough review processes though typically rigorous, we failed to catch this error by our naked eyes due to the compressed timeframe and multiple concurrent reviews. We have prepared a corrected version of Fig. 7B Untreated Day 12 which accurately reflects our findings and data discussed in the article, whereas the 7B Untreated Day 4 data is correct.[Formula presented] Fig. 7: (B) Skin histological studied under brightfield microscope (at 100× magnification) 4th day, 8th day and 12th day. The authors would like to apologise for any inconvenience caused. © 2024 Elsevier B.V.